Effect of adding perlite the soil in reducing water stress and its effect in some characteristics of the yield of three Genotypes of tomato - AL Shammari, Aziz Mahdi Abed; Abboud, Muhammad Ali; Hamdi, Ghassan Jaafar (Journal of agricultural, environmental and veterinary sciences, 2017)
The experiment was conducted during spring season of 2016 on the field of State Board of Agric., department of horticulture and landscape, college of agriculture, university of Diyala, Iraq. The objective of the experiment was investigated the interaction of three factors, three tomato Genotypes} Bobcat (V1), Finenss (V2) and Hadeer (V3){ irrigation (full irrigation 100 % (I1) and partial irrigation 50 % (I2) and addition three levels of perlite size- size perlite- soil (P0, P1 5 % and P2 10 %). Interaction among factors resulted in eighteen treatments, A split plot in randomized complete block design was used with three replications. Finenss Genotype had superior in maturity earliness fruit, fruit number, Bobcat genotype had significant differences in fruit weight average and height fruit weight. Plants irrigated with 50 % (partially) of irrigation (I2) had superiority in maturity earliness fruit. Addition of perlite with both levels P1 and P2 (no significant differences found between both) result in significant differences in comparison to control treatment in fruits number per plants, fruit weight average, yield per plant led to conclude, 5 % of perlite result in enhancing studied parameters. The study results showed superiority transactions morally V2I1P0 had superiority in maturity earliness fruit, V2I2P2 While treatments superiority significant in fruit number per plant, V1I1P2 While treatments superiority significant in fruit weight average and yield per plant and V1I1P2 While treatments superiority significant in height fruit weight.
Keywords: Genotypes; Perlite; Water stress; yield; Tomato